Highly efficient pollutants removal over Mo/Mo2C/CoAl-LDH heterostructure: photo-chemical co-driven peroxymonosulfate activation and singlet oxygen-dominated oxidative decomposition. (February 2023) - Fang, Hongjun; Ding, Jie; Feng, Xinzhen; Ji, Weijie; Au, Chak-Tong
Abstract: Novel Mo/Mo2 C/CoAl-LDH (CoAl layered double hydroxide) photocatalysts were fabricated through a hydrothermal route and applied for efficient PMS activation and typical pollutants (tetracycline/TC, ciprofloxacin/CIP, methylene blue/MB, congo red/CR and rhodamine B/RhB) degradation. Specifically, tetracycline removal efficiency of 99 % (TC, 20 mg/L) with a TOC mineralization efficiency of 65 % was achieved by the Mo/Mo2 C/CoAl-LDH/PMS/Vis system within 4 min-reaction, and the obtained reaction rate constant was 5.5 and 41.5 times greater than that of CoAl-LDH/PMS/Vis and Mo/Mo2 C/PMS/Vis system, respectively. The exceptional performance over this joint system was mainly attributed to the synergism of the MoCo dual active components and the involved photocatalysis. The quenching/ESR investigations clearly demonstrated that all of the generated species contributed to TC degradation, and among them the singlet oxygen showed the greatest impact. The toxicity assessment suggested that most of degraded intermediates become more eco-friendly to the environment. Moreover, the involved reaction mechanism and degradation pathways of TC were proposed and discussed in detail. This work provides a promising strategy for PMS activation and environmental purification through an integrated photo-chemical catalysis. Graphical abstract: Unlabelled Image Highlights: Novel Mo/MoC/CoAl-LDH heterojunction developed through a facile route. Efficient reaction system involves photocatalysis and PMS activation associating with the heterojunction. Enhanced visible light absorption, accelerated carrier kinetics, and enriched 1 O2 favors pollutants elimination. TC degradation routes and intermediates, and the toxicity assessments investigated in detail.